Pengaruh Pemberdayaan Masyarakat dan Kompensasi terhadap Kinerja Aparatur dengan Kepuasan Kerja sebagai Variabel Intervening: The Impact of Community Empowerment and Compensation on Employee Performance with Job Satisfaction as a Mediating Variable - Yetka Putri Yeni; Gus Andri; Hardinalis Kobal (Universitas Sumatera Barat, 2026)
This study aims to determine the effect of community empowerment and compensation on performance with job satisfaction as a mediating variable. The research method is quantitative with a survey approach using a sample of 208 people. Data collection is a questionnaire and PLS-SEM data analysis using the SmartPLS 4 application. The results of the study directly show that community empowerment, compensation, and job satisfaction have a positive and significant effect on the performance of village government. Community empowerment and compensation have a positive and significant effect on job satisfaction of village government. Indirect effects are found that job satisfaction is able to provide mediation on community empowerment on the performance of village government, while job satisfaction is not able to provide mediation on compensation on employee performance. The results of the determination coefficient test found that 40.9% (Weak) of the variance in job satisfaction is explained by community empowerment and compensation. Furthermore, 49.1% (Weak) of the performance variance is explained by community empowerment and compensation.